PELATIHAN BAHASA INGGRIS BAGI REMAJA SMP/SMA DESA LOYOK OLEH KKN-PMD UNIVERSITAS MATARAM 2023 - Solihah, Maulida; Hidayat, Rizky; Jannah, Miftahul; Febriana, Rista; Sofiatuddin, Baiq; Gunawan, M. Haerul; Suazhari, Muhammad Adam; Andini, Ayu Fitri; Aimar, Lalu Muhammad Fascal; Haerunnisa, Baiq Vidia; Wardoyo, Eustachius Hagni (Universitas Mataram, 2023)
Loyok Village is one of the Tourism Villages in Sikur District, East Lombok Regency. Many tourists come both from within and outside the country to see and enjoy the tourist objects in Loyok Village such as the woven bamboo art shop and the beautiful views of the rice fields. The English language training activities conducted by the University of Mataram KKN-PMD 2023 aim to improve English language skills for junior high/high school youth in Loyok Village. It is hoped that this capacity building will benefit the people of Loyok Village to make it easier for them to communicate with foreign tourists who come to Loyok Village. The training was attended by 23 representative participants from each hamlet in Loyok Village. This training includes several Speaking materials such as Greeting, Asking and Giving Opinion, Agree and Disagree, and Asking and Giving Direction. This training activity is carried out for 3 weeks, namely every Wednesday, Thursday and Friday. This English training activity brings directly tutors who are experienced in speaking English.